2012
DOI: 10.1016/j.juro.2011.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Time for Improvement in Semen Parameters After Varicocelectomy

Abstract: Sperm parameters improve by 3 months after varicocele repair and then do not improve further. This finding should allow physicians to decide quickly if varicocelectomy has been effective and, then, if required, plan on the use of other therapies to manage the couples' infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 29 publications
6
37
2
Order By: Relevance
“…The 71 patients in this study were classified into 3 groups according to baseline TMSC values before varicocelectomy; however, time-dependent changes in semen parameters in these 3 groups appeared to be similar to those in the overall cohort of the included patients, which were also supported by the previous study reported by Al Bakri et al 13 These findings suggest that semen parameters may be likely to exhibit uniform timedependent changes after varicocele repair, irrespective of baseline TMSC values before surgery.…”
Section: Commentsupporting
confidence: 85%
See 2 more Smart Citations
“…The 71 patients in this study were classified into 3 groups according to baseline TMSC values before varicocelectomy; however, time-dependent changes in semen parameters in these 3 groups appeared to be similar to those in the overall cohort of the included patients, which were also supported by the previous study reported by Al Bakri et al 13 These findings suggest that semen parameters may be likely to exhibit uniform timedependent changes after varicocele repair, irrespective of baseline TMSC values before surgery.…”
Section: Commentsupporting
confidence: 85%
“…Despite the simultaneous assessment of patients treated with embolization and varicocelectomy based on semen analyses at 3 and 6 months after varicocele repair, Al Bakri et al 13 reported findings similar to those in the present study. Furthermore, Tarhan et al 19 showed the time-dependent changes in testicular blood flow measured by color Doppler sonography, which seem to be proportional to those in the semen parameters presented in our study.…”
Section: Commentsupporting
confidence: 76%
See 1 more Smart Citation
“…In humans, the entire spermatogenic process takes approximately 64 days [73]. Studies evaluating the time interval between varicocelectomy and improvements in semen parameters revealed that sperm parameters improved during the first 3 months after varicocele repair, but did not show further improvements thereafter [7475]. Correspondingly, the ASRM Practice Committee has stated that improvements in semen parameters are typically seen after 3 to 6 months [12].…”
Section: Time Interval Between Varicocele Repair and Improvements In mentioning
confidence: 99%
“…Nevertheless, contrarily to the generally admitted idea that following varicocele treatment, semen improvement occurs progressively during the first year, we observed for all parameters (concentration, motility, vitality, normal forms and TMSC) a sharp rebound at 3 months, followed by a slight decrease but a level at the last analysis remaining higher than preoperatively. Recently Al Bakri et al reported similarly, that sperm parameters improve by 3 months following varicocele repair and then no more improvement by 6 months or longer [30]. The cause of such phenomenon remains unclear.…”
Section: Discussionmentioning
confidence: 99%